Clinical characteristics of a male child with non-classic lipoid congenital adrenal hyperplasia and literature review - Lu, Wenli; Zhang, Tingting; Zhang, Lidan; Wang, Xueqing; Lv, Sheng; Wang, Junqi; Ye, Lei; Xiao, Yuan; Dong, Zhiya; Wang, Wei; Sun, Shuoyue; Li, Chuanyin; et al. (Frontiers in Endocrinology, 2022)
Abstract: Background: Congenital lipoid adrenal hyperplasia (LCAH) is a rare and severe disorder, which is caused by mutations in the steroidogenic acute regulatory protein (StAR). Non-classic LCAH is defined as late-onset glucocorticoid deficiency and even complete male external genitalia in 46，XY individuals. However, to date, few cases of non-classic LCAH have been reported. Methods: It was attempted to describe clinical characteristics of a male child with complete male external genitalia, in terms of age of onset, adrenal function, and biochemical indicators. Previously reported cases were also reviewed to investigate the relationship of age of onset with enzymatic activity in non-classic LCAH. Results: The patient with complete male external genitalia was diagnosed with non-classic LCAH, in which the reason for his referral to a local hospital at the of age 1.25-year-old was progressive skin hyperpigmentation and micro-penis, and plasma adrenocorticotropic hormone (ACTH) level was elevated to higher than 1250 pg/ml. The compound heterozygous mutations c.772C>T/c.562C>T in STAR gene were identified via genetic testing. The literature review resulted in identification of 47 patients with non-classic LCAH from 36 families. The mutational analysis showed that c.562C>T mutation was prevalent in patients with non-classic LCAH, accounting for 37.2% of the total mutant alleles, which could reflect the founder effect on the non-classic LCAH population. In total, 28 46, XY patients were reported, including 22 (78.5%) cases with complete male external genitalia and 6 (21.5%) cases with different degrees of hypospadias. Conclusion: The clinical phenotypes of non-classic LCAH are highly variable. Routine physical examination, laboratory measurement, genetic testing, and importantly, enzymatic activity assay may facilitate the early diagnosis of non-classic LCAH. The age of Primary adrenal insufficiency(PAI) onset may not be a diagnostic basis for non-classic LCAH, and enzymatic activity assay determination may be more effective.